A new species of the genus Plumaroides Brothers (Hymenoptera, Chrysidoidea, Plumariidae) from Santiago del Estero, Argentina: male and female description - Diez, Patricia A. (Zootaxa, 2008)
This work describes a new species of the genus Plumaroides Brothers called P. tiphlus, sp. nov. This new species was collected in the province of Santiago del Estero, Argentina. Both sexes are described for this species, and this work represents the first association and description of the female for this genus.